1982
DOI: 10.1210/endo-110-6-2097
|View full text |Cite
|
Sign up to set email alerts
|

Adrenocorticotropin,β-Endorphin, and Corticosterone Secretion in Brattleboro Rats*

Abstract: Brattleboro rats which lack endogenous vasopressin have been used to study the role of vasopressin as a corticotropin-releasing factor. Plasma ACTH, beta-endorphin, and corticosterone were measured by RIA in male and female Long-Evans and Brattleboro rats under the following conditions: unstressed, after ether stress, after nicotine injection, and after adrenalectomy. A significant reduction in the ACTH, beta-endorphin, and corticosterone responses to the different experimental procedures was observed in the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Assays. Corticosterone was assayed in plasma and urine (after ethanol or dichloromethane extraction, respectively) using a radioimmunoassay previously described (16). Adrenals were dissected free of fat, weighed to the nearest milligram, and homogenized in a solution of 0.9% NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Assays. Corticosterone was assayed in plasma and urine (after ethanol or dichloromethane extraction, respectively) using a radioimmunoassay previously described (16). Adrenals were dissected free of fat, weighed to the nearest milligram, and homogenized in a solution of 0.9% NaCl.…”
Section: Methodsmentioning
confidence: 99%
“…Although shown to be an ACTH secretagogue, the physiologic role played by VP in the regulation of ACTH secretion is uncertain (3,19,20). Studies in Brattleboro rats, which genetically lack VP but have ACTH-releasing activity in extracts of their hypothalami and secrete ACTH in response to stress, suggest that VP plays only a minor role (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, an hypothesis has emerged that VP may modulate the ACTH response to CRF and may be only one of several factors influencing ACTH secretion (3,19,23,24). Early studies showed that low doses of VP potentiated the ACTH-releasing activity of hypothalamic extracts in rats (25).…”
Section: Introductionmentioning
confidence: 99%
“…A spontaneous point mutation resulted in an altered AVP precursor which was unable to enter the secretory pathway (Evans et al, 2000, Surget andBelzung, 2008). As a result, homozygous AVP-deficient Brattleboro rats (KO) show diminished HPA axis responses to different acute stressors (Wiley et al, 1974, Conte-Devolx et al, 1982, Fink et al, 1992, accompanied by reduced depressive-and anxiety-like behavioral profile (Mlynarik et al, 2007). More specifically, AVP-deficient rats showed higher preference for a sweet solution, spent considerably shorter time immobile in the FS test and less time self-grooming on the elevated plus maze (EPM) accompanied by a higher level of dexamethasone-induced suppression of corticosterone response to restraint stress.…”
mentioning
confidence: 99%